2006
DOI: 10.1044/1092-4388(2006/054)
|View full text |Cite
|
Sign up to set email alerts
|

Tense and Agreement Morphemes in the Speech of Children With Specific Language Impairment During Intervention: Phase 2

Abstract: Although the results provide clear evidence for intervention effects, it appeared as if maturational factors also played a role. The findings are discussed in terms of their implications for treatment and for characterizing development in SLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
83
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 44 publications
7
83
0
3
Order By: Relevance
“…However, the present study indicated that generalization of morpheme use can be seen in less than 8 weeks. In addition, accuracy for elicited generalization probes obtained in the present study was comparable to those seen after 6 months of treatment in Leonard et al (2006). If this finding generalizes to larger studies of children with cochlear implants, this method could prove to be a relatively efficient means of producing change in morpheme use for these children.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, the present study indicated that generalization of morpheme use can be seen in less than 8 weeks. In addition, accuracy for elicited generalization probes obtained in the present study was comparable to those seen after 6 months of treatment in Leonard et al (2006). If this finding generalizes to larger studies of children with cochlear implants, this method could prove to be a relatively efficient means of producing change in morpheme use for these children.…”
Section: Discussionsupporting
confidence: 53%
“…The children in their studies made greater gains in use of the grammatical target after 10 months of treatment than the children who received treatment for 5 months. In addition, Leonard, Camarata, Brown, and Camarata (2004) and Leonard et al (2006) used conversational recast treatment for a total of 48 sessions over 3 months, and then continued to a total of 96 intervention sessions over 6 months. Children showed modest gains after 3 months but continued to improve with additional time.…”
Section: Discussionmentioning
confidence: 99%
“…The first two phases were presented in this Journal by Leonard, Camarata, Brown, and Camarata (2004) and Leonard, Camarata, Pawłowska, Brown, and Camarata (2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies (Leonard et al, 2004;Leonard et al, 2006), children with SLI aged 3 to 4 years participated in one of two treatment conditions. One condition focused on the target morpheme third person singular -s; the other condition centered on the target morphemes auxiliary is/are/was.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation